Refining diagnostic criteria for paediatric bronchiectasis using low-dose CT scan. (October 2021) - Wu, Johnny; Bracken, Jennifer; Lam, Adrienne; Francis, Kate L.; Ramanauskas, Fiona; Chang, Anne B.; Robinson, Phil; McCallum, Paul; Wurzel, Danielle F.
Abstract: Background: There is a current lack of consensus amongst paediatric radiologists and respiratory paediatricians as to the correct CT definition of bronchiectasis in children. Using contemporary low-dose CT, our objectives were to determine the upper limit of normal for broncho-arterial ratio (BAR) in children and to evaluate the effect of age and general anaesthesia. Methods: Measurements of 330 broncho-arterial ratios from 51 children (0–19 years) undergoing low-dose CT chest for non-respiratory indications were performed by 3 blinded observers (two radiologists, one respiratory physician) using four different methods. Inter-observer reliability, mean BAR and reference ranges (mean±2SD) were calculated. Correlation between age and BARs were examined. Mean BAR for CT under general anaesthesia and CT awake were compared. Results: Inter-observer correlation was extremely high for all measurements (0.93–0.97). There was a weak positive correlation between age and BAR in the CT-awake group (r = 0.33, 95%CI: 0.03–0.57; p = 0.031) using the inner-bronchial wall to artery, short-axis measurement. CT under general anaesthesia showed significantly higher BAR compared to CT-awake [mean difference 0.13 (95%CI: 0.05–0.22; p = 0.004)]. For the CT-awake group, the mean BAR was 0.65 (range: 0.42 to 0.89), with no child having a BAR above 0.9. Conclusion: Using a standardised approach, we have shown that a broncho-arterial ratio above 0.9 in children undergoing awake CT is abnormal and suggests airway widening or radiological bronchiectasis. Children undergoing CT under anaesthesia have higher BARs than those undergoing awake CT. A weak positive correlation between broncho-arterial ratio and age was observed, hence, age-adjusted cut-offs for BAR warrant further study. Highlights: There is a lack of consensus regarding the radiological criteria for defining bronchiectasis in children using low-dose CT. Early diagnosis of bronchiectasis will facilitate interventions to slow or reverse disease progression in children. Children have lower broncho-arterial ratios than adults; a ratio >0.9 in children is abnormal. Raised broncho-arterial ratio in the correct clinical setting suggests bronchiectasis. Computer-assisted measurement of broncho-arterial ratio will facilitate establishment of age-adjusted cut-offs in children.